Analysis the factors influencing consumers’ adoption of mobile banking application services among the communities in Universiti Teknologi Mara Puncak Alam / Nur Hidayah Razali. - Razali, Nur Hidayah (2019)
Commercial banks in Malaysia have been trying for several years to introduce mobile banking systems in order to reduce their transaction costs and improve their services. Mobile Banking refers to the production and availability with mobile telecommunications equipment of banking and financial services. Thus, the objectives of this research are to analysis the factors that influencing consumers’ adoption and to determine the factors that affecting consumers’ intention in using mobile banking application among communities in UiTM Puncak Alam. There are 68 respondents that participate in this research where all the respondents are students, lecturer and staff at MARA University of Technology Malaysia, Puncak Alam. This research analyzing by using Statistical Product for Service Solutions (IBM SPSS Statistics 21). From the finding it can be said that the main factors that influencing consumers’ adoption are mobile banking is useful and easy to use and also it provided modern technology to the customers. While, the factors that affecting consumers intention is in making a money transaction using mobile banking application is faster than using Auto-Teller Machine (ATM). It also can be seen that the factors that can be related in using mobile banking application is the range of age of the respondents.